2021
DOI: 10.20525/ijrbs.v10i4.1212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of workplace loneliness and perceived organizational support towards intention to leave mediated by organizational commitment

Abstract: The aim of this research is to examine and analyze effects of workplace loneliness and perceived organizational support towards Intention to Leave mediated by organizational commitment. This research was conducted on the employees of securities company that are part of Indonesian Stock Exchange (BEI), specifically located in D.I. Yogyakarta and Central Java, with a total sample of 101 respondents. The data analysis used for this research is quantitative method of Structural Equation Modeling (SEM) with result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Similar to the results of the study, Özçelik & Barsade [45] also concluded that alienation in organizations will reduce emotional bonds and cause a lack of efficiency and performance. Wahyuni and Muafi [46], in their study on stock market employees in Indonesia, found that organizational loneliness caused a decrease in the perception of organizational support, and in this case, it caused job destruction in the employee. In addition, studies in the literature show that loneliness in organizations can negatively affect variables such as physical health, mental well-being, job commitment, organizational performance and organizational citizenship, and the desire to leave [47,48,49,50,51,46].…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to the results of the study, Özçelik & Barsade [45] also concluded that alienation in organizations will reduce emotional bonds and cause a lack of efficiency and performance. Wahyuni and Muafi [46], in their study on stock market employees in Indonesia, found that organizational loneliness caused a decrease in the perception of organizational support, and in this case, it caused job destruction in the employee. In addition, studies in the literature show that loneliness in organizations can negatively affect variables such as physical health, mental well-being, job commitment, organizational performance and organizational citizenship, and the desire to leave [47,48,49,50,51,46].…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Wahyuni and Muafi [46], in their study on stock market employees in Indonesia, found that organizational loneliness caused a decrease in the perception of organizational support, and in this case, it caused job destruction in the employee. In addition, studies in the literature show that loneliness in organizations can negatively affect variables such as physical health, mental well-being, job commitment, organizational performance and organizational citizenship, and the desire to leave [47,48,49,50,51,46]. Individuals who are isolated in organizations feel rejected and tend to get bored and get rid of their environment [52].…”
Section: Conclusion and Discussionmentioning
confidence: 98%